Vaping-induced metabolomic signatures in the circulation of mice are driven by device type, e-liquid, exposure duration and sex. Issue 3 (12th July 2021) - Moshensky, Alexander; Du, Mulong; Shin, John; Advani, Ira; Gunge, Deepti; Mathew, Denzil; Alkolla, Rita; Du, Ashley; Javier, Christian; Ma, Lauren; Tran, Albert; Nguyen, Nicholas; et al.
Electronic (e)-cigarette devices have evolved rapidly since the modern version was introduced in 2007 [1, 2]. Inhalation of aerosols generated by these devices has been tied to multiple lung diseases, and diseases and pathology outside the lungs, while the underlying mechanisms driving e-cigarette-associated pathology remain unknown [3–7]. Each type of vaping device (vape pen, box Mod and JUUL), as well as nicotine and flavourings, induces a disparate metabolite profile or signature, such that each device and liquid is likely to lead to its own set of health effects https://bit.ly/3eExKzi